Association Between Immigration History and Inflammatory Marker Profiles Among Older Adult Mexican Americans. (2nd January 2018) - Martin, Chantel L.; Haan, Mary N.; Fernandez-Rhodes, Lindsay; Lee, Anne; Aiello, Allison E.
ABSTRACT: Foreign-born Hispanics have better cardiometabolic health upon arrival in the US than their US-born counterparts, yet this advantage diminishes as duration of residence in the US increases. Underlying mechanisms explaining this paradox have been understudied. Using data from the Sacramento Area Latino Study on Aging (SALSA), this study examined immigration history (immigrant generation and duration of US residence) in relation to biomarkers of inflammation (interleukin-6 (IL-6), soluble forms of type 1 and 2 receptors of tumor necrosis factor-alpha (sTNF-R1 and sTNF-R2), C-reactive protein (CRP), leptin, adiponectin) in a sample of 1, 290 predominantly Mexican-origin immigrants. Second and ≥3rd generation immigrants had higher IL-6 and leptin levels than 1st generation immigrants living in the US for less than 15 years (2nd generation percent difference = 45.9; 95% CI: 24.7, 70.7 and 3rd generation percent difference = 41.8; 95% CI: 17.7, 70.4). CRP and sTNF-R1 levels were higher among ≥3rd generation immigrants than 1st generation immigrants with less than 15 years of US residency. Worse inflammatory profiles were observed among Mexican-origin immigrants with longer US immigration histories, independent of health, and behavioral factors. Additional research is warranted to understand the factors that shape trajectories of biological risk across generations of Hispanics.